Józef Darski – Sein Leben und sein Werk - Taborek, Janusz (Studia Germanica Posnaniensia, 2018)
In this contribution, we present the life and work of Józef Darski (1941–2016), a Polish German Philologist, Linguist and Grammarian. The research profile of Józef Darski contains such fields of interest as: dialectology, German grammar, contrastive German-Polish grammar as well as German as a foreign language. The most important work, which influenced his entire research output, was Linguistisches Analysemodell. Definitionen grundlegender grammatischer Begriffe. That model includes the analysis of phonological, morphological and syntactic levels of language.